The word ‘Allah’ and its usage: an analysis into the history of the Arabic language - Yaacob, Solehah@Nik Najah Fadilah (CASIS, Universiti Teknologi Malaysia, 2015)
The issue of the word ‘Allah’ is evidence that Malaysia’s society is not yet deeply enlightened on the origins of the Arabic language, that is, the language of the Qur’an. To explain this issue in more details towards the origins of this language of the Qur’an, research on the word ‘Allah’ is sample proof that the nahw systems have been practiced, thus the word ‘Allah’ through an Arabic linguistic nahw approach has to be phrased to determine when did this word appear. Ibnu Manzur, in his book Lisaan al- Arab, had discussed the meaning of the word ‘Allah’ in depth. The word ‘Allah’ in fact originates from the word إِلاَهٌ from the wazn فِعَالٌ that then became wazn مَفْعُوْلٌ or مَأْلُوْهٌ meaning ‘who is worshipped’. Sibawaih had also mentioned, in his book al-Kitab, that pre-Islamic Arabs had used the word لاهٌ , with omission of the second `Lam` in this word ‘Allah’. This means that when the word لاهٌ is perfect or complete in nominative rules it is pronounced as `الله ` where this is only used in the Qur’an. Therefore, Books before the Qur’an had not used the word ‘الله’. Thus research such as this one has to be discussed in details, since this word ‘Allah’ involves the Aqidah of the Muslim Ummah.